Efektivitas Program Pusat Pelayanan Keluarga Sakinah dalam Upaya Mewujudkan Keluarga Sakinah - Dama, Fahrun (HOKI : Journal of Islamic Family Law, 2024)
The formation of a sakinah family is one of the goals of marriage. In its implementation, married couples must build positive and harmonious patterns of interaction in order to create harmony in the household. The type of research used is empirical legal research, which aims to see how the implementation of the pusaka sakinah program is carried out at the KUA of Paciran District, Lamongan Regency. Data collection is based on interviews with selected resource persons who understand and are directly related to the program, namely the Head of the KUA, the Penghulu, and the Extension Officer. The results showed that the implementation of the sakinah heirloom program at the KUA of Paciran District, Lamongan Regency based on analysis in accordance with Soerjono Soekanto's theory of legal effectiveness, has been carried out well but not all of them are optimal because the existing rules do not yet have firmness, such as the inclusion of the sakinah heirloom program as a requirement for divorce registration, in terms of the community, the community is enthusiastic about this program.